Failure Behavior of Unidirectional Composites under Compression Loading: Effect of Fiber Waviness - Nair, Swaroop Narayanan (2018)
The key objective of this work is to highlight the effect of manufacturing-induced fiber waviness defects on the compressive failure of glass fiber-reinforced unidirectional specimens. For this purpose, in-plane, through-thickness waviness defects (with different waviness severities) are induced during the manufacturing of the laminate. Numerical and experimental results show that the compressive strength of the composites decreases as the severity of the waviness defects increases. A reduction of up to 75% is noted with a wave severity of 0.075. Optical and scanning electron microscopy observations of the failed specimens reveal that kink-bands are created in the wavy regions and lead to failure.